Prevalence and Determinants of Minimum Acceptable Diet Among Children Aged 6–23 Months in Sub-Saharan Africa: The Demographic and Health Surveys, 2019–2020. (14th June 2022) - Ba, Djibril; Ssentongo, Paddy; Lekoubou, Alain; Holland, Nicole; Maiga, Mamoudou; Gao, Xiang
Abstract: Objectives: Lack of adequate nutrition during the first two years of a child is associated with inadequate brain development, undernutrition, increased risk of chronic diseases and mortality. We thus conducted a population-based study to examine the prevalence of minimum acceptable diet (MAD), a composite indicator combining minimum dietary diversity (MDD) and minimum meal frequency (MMF), in sub-Saharan Africa (SSA) and associated socio-demographic-economic factors. Methods: The present analysis was based on the most recent Demographic and Health Surveys (DHS) surveys (2019–2020). Included were 5, 832 children aged 6–23 months old living SSA countries (Gambia, Liberia, Rwanda). MAD for breastfed children 6–23 months is achieved if a child met both the MDD and MMF criteria. For non-breastfed children 6–23 months, a child had to meet the MDD excluding dairy products, the MMF and two or more milk feeds. A multivariable logistic regression model was used to identify independent factors associated with odds of achieving MAD (yes/no). Results: The overall weighted prevalence of achieving MAD was low, 14.2% (95% CI: 12.9–15.6), ranging from 3.2% in Liberia to 21.4% in Rwanda. Independent factors associated with MAD were: older age (adjusted odds ratio (aOR) = 1.65 (95% CI: 1.32–2.06, for 12–17 months vs. 6–11 months), mothers who belong to highest households wealth index (aOR = 1.80 for the highest vs. lowest wealth index status, 95% CI: 1.35–2.39), and mothers with secondary or higher levels of education (aOR = 1.77, 95% CI: 1.32–2.37) compared with those with no education. Mothers who had access to media (radio) and those who visited a healthcare facility in the last 12 months were also associated with higher odds of MAD in children. Conclusions: In this study, the prevalence of MAD among children aged 6–23 months in SSA was low and varies substantially across countries. Mothers' socioeconomic and education status were some of the leading determinants of MAD. Comprehensive nutritional education programs targeting mothers are critically needed to improve MAD in SSA and prevent undernutrition. Funding Sources: There was no external or internal funding to support this study.